Distribution of Diseases and their Prescription Pattern at Outpatients Department of Gynecology and Obstetrics in a Tertiary Care Hospital in Bangladesh - Shahnawaz, Shabrina Shammi; Sharif, Md Hasan; Afrin, Tasnin; Ferdusi, Fatema; Rahman, Kazi Foyzur; Habib, Anwar (Journal of Current and Advance Medical Research, 2023)
Background: Different gynaecological and obstetrics conditions are commonly encountered by the physicians in the outdoor patient. Objective: The purpose of the present study was to observe the distribution of diseases and their prescription pattern at outpatients Department of Gynaecology and Obstetrics in a tertiary care hospital in Bangladesh. Methodology: This cross-sectional study was carried out among patients attending the outpatient’s department (OPD) of Obstetrics and Gynaecology from October 2014 to April 2015 in Rajshahi Medical College and Hospital, Rajshahi, Bangladesh. The demographic details, average number of drugs per prescriptions, percentage of drugs prescribed by generic names, percentage of encounters with an antibiotic and an injection prescribed, percentage of drugs prescribed from essential drug list (EDL) of Bangladesh, percentage of encounters with prescription of antiulcerant, NSAID, multivitamin and multimineral, iron preparation and a calcium preparation were noted. Results: A total number of 384 prescriptions were collected from Out Patient Department of Obstetrics and Gynaecology of Rajshahi Medical College and Hospital, Rajshahi, Bangladesh. Among 384 prescriptions date, name and age of the patient was written in 384 prescriptions which was 100.0% cases. Weight was written in 190(49.5%) and absent in 194(50.5%) prescriptions. Strength of drugs were written in 11(2.9%) prescriptions and not written in 373(97.1%) prescriptions. Duration of treatment was written in 100.0% prescriptions. Subscription is absent in 100.0% prescriptions. Direction to the patient was present in all prescriptions, but follow up advice were written only in 9(2.3%) prescriptions. Sign present in all prescriptions. There were about 169(44.0%) prescriptions have written the diagnosis and 215(56.0%) prescriptions did not have any diagnosis written. Conclusion: In conclusion the date, name and age of the patient are written in all prescriptions and strength of drugs are absent in almost all prescriptions. Journal of Current and Advance Medical Research, January 2023;10(1):13-18